One island, many voices : conversations with Cuban-American writers - Rio, Eduardo del, 1960- (University of Arizona Press, 2008)
Cuban-American writers have been studied primarily within the context of Latino literature as a whole. Seeing a need to distinguish and define this unique literary perspective, Eduardo del Rio selected twelve important well-known authors and conducted interviews. He chose writers who were born in Cuba but have lived in the United States for a significant amount of time and whose works include themes he considers elemental to Cuban-American literature: identity, duality, memory, and exile. But rather than a cohesive, homogeneous group, these conversations unveiled a kaleidoscope of individuality, style, and motive. The authorsu2019 bonds to Cuba inform their creative work in vastly different ways, and attempts to categorize their similarities only highlight the range of character and experience within this assemblage of talented writers. From playwright Dolores Prida to author and literary critic Gustavo Pérez Firmat, these voices run the gamut of both genre and personality. In addition to the essential facts of literary accomplishment, the interviews include a wealth of insight into each writeru2019s history, motivations, concerns, and relationship to language. These personal details serve to humanize and illuminate the unique circumstances and realities that have shaped both the authors and their work. What del Rio has ultimately brought together is a series of intimate sketches that will not only serve as an important reference for any discussion of the literature but will also help readers to develop for themselves a sense of what Cuban-American writing is, and what it is not.